Australian First-Year Nursing Student Knowledge and Attitudes on Pressure Injury Prevention: A Three-Year Educational Intervention Survey Study - Carey Mather; Angela Jacques; Sarah J. Prior (MDPI AG, 2022)
Pressure injury prevention is a significant issue as pressure injuries are difficult to heal, painful, and create clinical complications for patients. The aim of this study was to investigate knowledge and attitudes of first-year nursing students to pressure injury prevention, and to explore whether additional educational interventions augmented learning. A previously validated online survey was administered to three cohorts of first-year nursing students in 2016, 2017 (after additional online education), and 2018 (after further simulation education), and a subsequent comparative analysis was undertaken. Overall, the knowledge of students about pressure injury was low with measures to prevent pressure injury or shear achieving the lowest score (<50%). Students aged over 25 years (p < 0.001) and men (p = 0.14) gained higher attitude scores. There were significant differences for mean knowledge scores between the 2016 and 2018 cohorts (p = 0.04), including age group (p = 0.013) and number of clinical training units undertaken (p = 0.23). The 2016 cohort scored consistently lower in the attitude survey than both other cohorts (p < 0.001). Online resources and simulation experiences marginally improved knowledge and improved attitudes towards prevention of pressure injury. Nursing curricula should include targeted education to ensure student nurses are adequately prepared to prevent pressure injury through understanding of aetiology and risk assessment.